2022
DOI: 10.3390/gels8100684
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Textile Waste Fibers Aerogels with Excellent Oil/Organic Solvent Adsorption and Thermal Properties

Abstract: In recent years, the treatment of textile waste has attracted more and more attention around the world. The reuse of textile waste can contribute to the reduction of carbon emissions and the sustainable development of the economy. Herein, we proposed a facile and cost-effective approach to fabricating aerogel by using textile waste fibers as the matrix and polyvinyl alcohol (PVA) and glutaraldehyde (GA) as crosslinking agents. After being modified with methyltrimethoxysilane (MTMS) via chemical vapor depositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 67 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…literature is available about the reuse of aerogels close to real-world conditions, namely the purification of oil from water and the multiple use of aerogels [7][8][9]. Currently, the mechanical properties of aerogels are evaluated using dry samples and only one-time compression [1,10,11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…literature is available about the reuse of aerogels close to real-world conditions, namely the purification of oil from water and the multiple use of aerogels [7][8][9]. Currently, the mechanical properties of aerogels are evaluated using dry samples and only one-time compression [1,10,11].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the excellent properties of aerogels, which include high porosity, low density, and high surface area [5], the mechanical properties of cellulose-based aerogels still need to be improved for use at high temperatures or organic solvent removal [6]. Little literature is available about the reuse of aerogels close to real-world conditions, namely the purification of oil from water and the multiple use of aerogels [7][8][9]. Currently, the Gels 2024, 10, 135 2 of 14 mechanical properties of aerogels are evaluated using dry samples and only one-time compression [1,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Due to climate change and increasing concerns and awareness regarding the environment and sustainability, the problems related to managing solid waste are pain points of modern society [34]. The most rapid way to get rid of textile waste is by incineration, but it produces toxic gases including carbon dioxide, polycyclic aromatic hydrocarbons, and benzene derivatives [35]. Another method of waste management is dumping into the ground called landfills.…”
Section: Global Environmental Impact Of Wastementioning
confidence: 99%
“…The United States Environmental Protection Agency (USEPA) has also established waste regulation directives including hazardous waste management, recycling, atomic energy, clean air, chemical safety, marine protection, oil pollution, pollution prevention, and toxic substances [43]. The regularization of waste management policies is becoming mature and strict especially for organic wastes; for example, in 2016, the European Union's legislation regulated landfilling of organic materials as illegal and almost all textile materials are organic [35].…”
Section: Legislation Related To Waste Materialsmentioning
confidence: 99%
“…Dong et al showed composite gel from textile waste fiber and poly(vinyl alcohol), crosslinked first by the formation of hydrogen bonding on the surface of fiber followed by the covalent linkage of the acetal functional group by glutaraldehyde. The merit properties of such aerogels from textile waste fiber expands the application perspectives associated with recycled materials [ 9 ]. Racles et al demonstrated a new method to stabilize the emulsion aqueous phase within toluene sol, followed by the UV-triggered thiolene crosslinking of vinyl-polysiloxane to form emulsion gels [ 10 ].…”
mentioning
confidence: 99%